1989
DOI: 10.1007/bf00451649
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of (glycolato-0,0?)-diammine platinum (II), a new platinum derivative, in comparison with cisplatin and carboplatin

Abstract: The pharmacokinetics of (glycolato-0,0')-diammine platinum (II) (254-S; NSC 375101D), one of the new platinum analogues, was examined in a phase I study of this drug and compared with that of cisplatin and carboplatin. All drugs were given in short-term (30-min) i.v. drip infusions; the doses of 254-S, cisplatin, and carboplatin were 100, 80, and 450 mg/m2, respectively. Platinum concentrations in whole plasma, plasma ultrafiltrate, and urine were determined by atomic absorption spectrometry. After the infusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 9 publications
0
48
0
Order By: Relevance
“…However, in a steady state, kidney accumulation of cisplatin was higher, which may lead to renal toxicity. As nedaplatin disappears in plasma immediately after administration, the rate of kidney excretion may be higher than that of cisplatin, 24,25) contributing to a low kidney accumulation of nedaplatin. As another possibility, the renal cell level of nedaplatin may be lower than that of cisplatin, since it is speculated that cisplatin is ingested by the tubular epithelial cells via a transport system on the basolateral membrane of the kidney tubule.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a steady state, kidney accumulation of cisplatin was higher, which may lead to renal toxicity. As nedaplatin disappears in plasma immediately after administration, the rate of kidney excretion may be higher than that of cisplatin, 24,25) contributing to a low kidney accumulation of nedaplatin. As another possibility, the renal cell level of nedaplatin may be lower than that of cisplatin, since it is speculated that cisplatin is ingested by the tubular epithelial cells via a transport system on the basolateral membrane of the kidney tubule.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma concentration profile of unbound platinum after 254-S infusion has been reported to be similar to that of total platinum, and the protein binding of 254-S to be lower than that of CDDP (Ota et al, 1994). Nedaplatin has a short elimination half-life and a phamacokinetic profile similar to that of CBDCA (Sasaki et al, 1989). Nephrotoxicity and gastrointestinal toxicity often limits the clinical use of antitumour agents such as CDDP, but 254-S causes less nephrotoxicity and gastrointestinal toxicity than CDDP, although its haematological toxicity can be a limiting factor at high dosage, as found with CBDCA (Kameyama et al, 1990;Ota et al, 1992;Suzumura et al, 1989).…”
mentioning
confidence: 99%
“…To our knowledge, there has been no randomized controlled trial to determine an adequate infusion volume on the day of CDDP administration, and there is far less evidence for the amount of oral hydration required before or after the day of CDDP administration. A report on the pharmacokinetics of CDDP showed that the blood level of free CDDP, which causes renal toxicity, diminished below the limit of detection sensitivity on the day after CDDP administration [13], and it is thought that hydration on the day after CDDP administration may not be indispensable.…”
Section: Discussionmentioning
confidence: 99%